Case Report: Traumatic Carotid-Cavernous Fistula. Issue 1 (January 2016) - Pülhorn, Heinke; Chandran, Arun; Nahser, Hans; McMahon, Catherine
Abstract : Carotid-cavernous fistulae (CCFs) are a rare complication of head trauma, with potentially serious consequences. We report the case of a 45-year-old male patient who presented with posttraumatic CCF 2 months after sustaining a head injury. Appropriate imaging in the form of computed tomography of the head, magnetic resonance imaging of the head, and digital subtraction angiography of the intracranial vessels was performed, and the CCF was successfully coil embolized. This resulted in good resolution of the patient's symptoms. We discuss the cause, presentation, diagnosis, and treatment of CCFs. Carotid-cavernous fistulae are a rare sequela of craniofacial trauma; therefore, a high index of suspicion must be maintained to establish a diagnosis and prevent serious consequences.